In-hospital switching between adenosine diphosphate receptor inhibitors in patients with acute myocardial infarction treated with percutaneous coronary intervention: Insights into contemporary practice from the TRANSLATE-ACS study. Issue 6 (1st December 2015) - Bagai, Akshay; Peterson, Eric D; Honeycutt, Emily; Effron, Mark B; Cohen, David J; Goodman, Shaun G; Anstrom, Kevin J; Gupta, Anjan; Messenger, John C; Wang, Tracy Y
Abstract: Aims: While randomized clinical trials have compared clopidogrel with higher potency adenosine diphosphate (ADP) receptor inhibitors among patients with acute myocardial infarction, little is known about the frequency, effectiveness and safety of switching between ADP receptor inhibitors in routine clinical practice. Methods and results: We studied 11, 999 myocardial infarction patients treated with percutaneous coronary intervention at 230 hospitals from April 2010 to October 2012 in the TRANSLATE-ACS study. Multivariable Cox regression was used to compare six-month post-discharge risks of major adverse cardiovascular events (MACE: death, myocardial infarction, stroke, or unplanned revascularization) and Global Utilization of Streptokinase and t-PA for Occluded Coronary Arteries (GUSTO)-defined bleeding between in-hospital ADP receptor inhibitor switching versus continuation of the initially selected therapy. Among 8715 patients treated initially with clopidogrel, 994 (11.4%) were switched to prasugrel or ticagrelor; switching occurred primarily after percutaneous coronary intervention (60.9%) and at the time of hospital discharge (26.7%). Among 3284 patients treated initially with prasugrel or ticagrelor, 448 (13.6%) were switched to clopidogrel; 48.2% of switches occurred after percutaneous coronary intervention and 48.0% at hospital discharge. Switching to prasugrel or ticagrelor was not associated with increased bleeding when compared with continuation on clopidogrel (2.7% vs . 3.3%, adjusted hazard ratio 0.96, 95% confidence interval 0.64–1.42, p =0.82). Switching from prasugrel or ticagrelor to clopidogrel was not associated with increased MACE (8.9% vs . 7.7%, adjusted hazard ratio 1.06, 95% confidence interval 0.75–1.49, p =0.76) when compared with continuation on the higher potency agent. Conclusions: In-hospital ADP receptor inhibitor switching occurs in more than one in 10 myocardial infarction patients in contemporary practice. In this observational study, ADP receptor inhibitor switching does not appear to be significantly associated with increased hazard of MACE or bleeding.